A Multifactorial Analysis of Concessive Clause Positioning. Issue 4 (2nd October 2021) - Kang, Hui; Xu, Jiajin
ABSTRACT: Previous works have identified multiple factors and their interplay that condition the positioning of the concessive adverbial clauses. This study continues this line of research by 1) focusing exclusively on the positioning of although -led concessive adverbial clauses ( although -clauses hereafter) among different concessive clause relations; 2) supplementing the factor set with more linguistic features, such as sentence-initial adverbials and hedging terms; and, 3) extending and generalizing the scope of competition among semantic, discoursal and processing motivators to a higher-level competition between 'clarity' and 'processability'. Data were retrieved from 1, 738 concessive sentences of student argumentative essays from the BAWE and NESSIE corpora. Models were generated based on binary logistic regression and random forests. The results show that the motivator of the relationship between the although-clauses and their main clauses was the most significant variable in all models, denoting its priority in conditioning concessive clause positioning, under the Competition Model framework. Subordinate clause complexity and deranking (i.e. clauses that do not have a full verb) were the least significant among all motivating factors. Overall, clarity-related motivators outweigh processability-related ones, prioritizing clear meaning-conveying in competition with processing motivators.